Assessing the Use of Pet Fibre in Reinforcement of Lime Stabilised Soil - Caleb Asiimwe (Uganda Christian University, 2024)
The presence of poor subgrade materials, particularly clay soils, poses asignificant challenges in road construction due to swell and shrink under varying moisture levels. This leads to road cracks and failures requiring methods to enhance soil strength. Chemical and mechanical stabilization methods are commonly employed, with factors like plasticity index and particle size distribution crucial in selecting appropriate stabilizers. Lime and cement are favored for their ability to chemically stabilize such soils, though lime stabilization may exhibit drawbacks such as poor strength characteristics due to factors like carbonation and organic matter presence. This paper investigated the impact of varying PET fiber content added to lime-stabilized soil, analyzing its influence on soil strength. The study evaluates California Bearing Ratio (CBR) and Unconfined Compressive Strength (UCS) of the stabilized soil. Results indicate that soil stabilized with 6% lime alone falls short of minimum standard requirements, with a UCS below the necessary threshold of 0.5 MPa. However, incorporating PET fibers shows promise, with optimum strength improvement observed at 1.5% fiber content, yielding a UCS of 0.59 MPa and a 54% CBR. This indicated an improvement impact on mechanical properties, enhancing the performance of clay soils stabilized with lime. The study suggested a 6% lime and 1.5% rice husk ash blend enhances strength. It highlights PET fibers' potential in lime stabilization for road construction, addressing weak subgrade materials and promoting sustainable waste management, particularly plastic waste utilization. This combination offers a promising solution to road construction challenges.